2017
DOI: 10.1021/acsami.7b10180
|View full text |Cite
|
Sign up to set email alerts
|

Bilayered BMP2 Eluting Coatings on Graphene Foam by Electrophoretic Deposition: Electroresponsive BMP2 Release and Enhancement of Osteogenic Differentiation

Abstract: Recent development of three-dimensional graphene foam (GF) with conductive and interconnected macroporous structure is attracting particular attention as platforms for tissue engineering. However, widespread application of GF as bone scaffolds is restricted due to its poor mechanical property and inert surface character. To overcome these drawbacks, in this study, a bilayered biopolymer coating was designed and successfully deposited covering the entire surface area of GF skeleton. A poly(lactic-co-glycolic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…This table highlights the variation in mechanical properties due to testing mechanism, graphene synthesis methods, and the addition of natural and synthetic polymers. CVD GF has been shown to support the growth of ATDC5 chondroprogenitor cells, C2C12 mouse myoblast cells, [14] MC3T3-E1 osteoblasts [25] , hMSCs, [15]–[17][26] and neural stem cells. [18] The mechanical properties of CVD GF are dependent on both the template structure and the density of graphene deposited on the template.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This table highlights the variation in mechanical properties due to testing mechanism, graphene synthesis methods, and the addition of natural and synthetic polymers. CVD GF has been shown to support the growth of ATDC5 chondroprogenitor cells, C2C12 mouse myoblast cells, [14] MC3T3-E1 osteoblasts [25] , hMSCs, [15]–[17][26] and neural stem cells. [18] The mechanical properties of CVD GF are dependent on both the template structure and the density of graphene deposited on the template.…”
Section: Resultsmentioning
confidence: 99%
“…[24] GF’s surface chemistry can be altered using various biopolymers to tune its strength and surface energy characteristics to meet the requirements of different cell lines. [17][25][26] The electrical properties of GF allow for electro-mechanical stimulation and it has been shown that the conductivity of GF remains stable with no production of harsh byproducts, unlike conductive polymers. [27] Finally, graphene materials demonstrate antibacterial and antifungal properties in wound infection, suggesting potential for anti-infective properties in tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMPs play a critical role in cell proliferation, differentiation, apoptosis, body development, and organogenesis, and 15 of these known proteins have been found in humans . BMP2, BMP4, and BMP7 exhibit excellent osteogenic capacity that has been widely used in the clinics . However, nonfusion spine formation induced by BMP2 and BMP7 could be occasionally reported in the clinics .…”
Section: Introductionmentioning
confidence: 99%
“…22 BMP2, BMP4, and BMP7 exhibit excellent osteogenic capacity that has been widely used in the clinics. [23][24][25] However, nonfusion spine formation induced by BMP2 and BMP7 could be occasionally reported in the clinics. 26 Since BMP9 was discovered, it has received wide attention due to its higher ability to stimulate bone formation than other members of the BMP family.…”
Section: Introductionmentioning
confidence: 99%